Catalyst for preparing aromatic hydrocarbon by one-step hydrogenation of CO2 as well as preparation method and application of catalyst

By using a core-shell structure catalyst in the CO2 one-step hydrogenation process, combining the core layer of metal oxide and molecular sieve and the silica shell layer, the problems of low aromatic selectivity and yield are solved, and high-efficiency hydrogen is achieved Carbon conversion and atomic economy reduce side reaction generation.

CN119215971AActive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310779571.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
2043-06-28

AI Technical Summary

Technical Problem

In the existing CO2 one-step hydrogenation process, aromatic hydrocarbons are low and aromatic yields are low, and it is difficult to achieve high CO2 conversion and low CO selectivity at the same time.

Method used

A catalyst with a core-shell structure is used, which includes the core layer of metal oxide and molecular sieve and the shell layer of silica. The ratio of the characteristic peaks of metal hydroxyl and silicon hydroxyl groups is correctly verified by infrared spectroscopy to ensure low exposure to metal hydroxyl groups. The degree of encapsulation of silica shells is high, which inhibits side reactions and improves the efficiency of hydrogen-carbon conversion.

Benefits of technology

The aromatic selectivity and yield are significantly improved, the CO selectivity is reduced, the hydrogen and carbon atom utilization rate is improved, and the effects of high CO2 conversion and high aromatic selectivity are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215971A_ABST
    Figure CN119215971A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for preparing aromatic hydrocarbon through CO2 one-step hydrogenation as well as a preparation method and application of the catalyst. The catalyst has a core-shell structure and comprises a core layer at least containing a metal oxide and a molecular sieve and a shell layer of silicon dioxide. The catalyst provided by the invention regulates the reaction path, fully improves the hydrogen-carbon conversion efficiency and atom economy, and has the characteristics of high aromatic hydrocarbon selectivity, high aromatic hydrocarbon yield and low CO selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of one-step hydrogenation of CO2 to aromatics, and more specifically to a catalyst for one-step hydrogenation of CO2 to aromatics, and a preparation method and application thereof. Background Art

[0002] Aromatics play an indispensable role in the national economy, and traditional production routes rely on non-renewable resources such as petroleum. As petroleum resources become increasingly scarce, more and more research is devoted to developing new routes for the production of aromatics to reduce dependence on petroleum resources. Carbon dioxide is widely present in nature, and the greenhouse effect caused by large amounts of carbon dioxide emitted by processes such as fuel combustion and biological respiration is a serious environmental problem. Through carbon dioxide capture and catalytic conversion technology, the production of aromatics and other chemicals using carbon dioxide as a carbon source can achieve resource utilization of carbon dioxide, which can not only reduce carbon emissions and alleviate environmental pressure, but also serve as a sustainable resource alternative.

[0003] The routes for converting carbon dioxide to aromatics include Fischer-Tropsch synthesis routes and conversion routes via methanol intermediates. The former converts carbon dioxide into carbon monoxide through the reverse water gas shift reaction, and carbon monoxide is converted into hydrocarbon products through the Fischer-Tropsch synthesis reaction. Since the product distribution of this process follows the Anderson-Schulz-Flory distribution, the selectivity of aromatic products is low. Another indirect synthesis route based on the methanol platform can refer to the existing mature process, but the production route is longer and the equipment investment is higher in actual production. In order to overcome the shortcomings of the above two routes, a catalyst with carbon dioxide hydrogenation activity is coupled with a catalyst with aromatization activity, which can realize the one-step conversion of carbon dioxide and generate aromatics with high selectivity.

[0004] CN201810476839.0 and Nature Communications 2018,9,3457 respectively reported that zinc aluminum spinel and acidic molecular sieve coupling catalysts achieved nearly 80% aromatics selectivity in the CO2 conversion system, but it was difficult to simultaneously achieve high CO2 conversion and low CO selectivity, such as when the CO2 conversion rate was ~10%, the CO selectivity was about 60%, and the carbon conversion efficiency was low. CN107840778A provides a method for hydrogenating carbon dioxide to produce aromatics, which uses an iron-based and modified or partially modified molecular sieve catalyst as a catalyst. This method for hydrogenating carbon dioxide to produce aromatics improves the single-pass CO2 conversion rate and increases C 5+ The selectivity of hydrocarbons and aromatics in C 5+ The selectivity among hydrocarbons is high, but the selectivity among aromatics is low. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of low aromatic selectivity and low aromatic yield in the one-step hydrogenation of CO2 to aromatics reaction in the prior art, and provide a catalyst for one-step hydrogenation of CO2 to aromatics and its preparation method and application. The catalyst regulates the reaction path, fully improves the hydrogen-carbon conversion efficiency and atom economy, and has the characteristics of high aromatic selectivity, high aromatic yield and low CO selectivity.

[0006] In order to achieve the above objectives, the first aspect of the present invention provides a catalyst for one-step hydrogenation of CO2 to aromatics, the catalyst having a core-shell structure, including a core layer containing at least metal oxide and molecular sieve and a shell layer of silicon dioxide.

[0007] Furthermore, the catalyst has a silicon dioxide shell layer, has a high degree of encapsulation, and substantially contains no unbonded metal hydroxyl groups on the surface.

[0008] Furthermore, in order to reflect the degree of coating on the catalyst surface, after correction according to the metal-oxygen characteristic peak intensity, the metal hydroxyl characteristic absorption peak area in the infrared spectrum of the catalyst of the present invention is less than 0.1, with the metal hydroxyl characteristic absorption peak area in the infrared spectrum of the catalyst without the coating shell layer (i.e., the catalyst having only the core layer of the catalyst of the present invention but no shell layer) as 1. The metal hydroxyl absorption peak area of ​​less than 0.1 can indicate that the exposure degree of the metal hydroxyl is very low, the surface of the metal oxide is fully modified, and the side reactions such as the reverse water gas shift on the surface of the metal oxide are weakened, and the generation of by-products such as CO is inhibited.

[0009] Furthermore, the infrared spectrum of the catalyst detected an enhancement of the characteristic absorption peak of silanol groups belonging to silica, which also indicates that the silica shell has a high degree of wrapping and that the silanol groups of silica can cover the metal hydroxyl groups, which is beneficial to the effect of weakening side reactions.

[0010] Furthermore, based on the area ratio of the characteristic absorption peak of silanol group to the characteristic absorption peak of metal hydroxyl group in the infrared spectrum of the catalyst, the relative content of silanol group / metal hydroxyl group of the catalyst is 4.0-10.0.

[0011] Furthermore, the mass ratio of the core layer and the shell layer in the catalyst is (4:1) to (40:1), for example, it can be 4:1, 6:1, 8:1, 10:1, 12:1, 14:1, 16:1, 18:1, 20:1, 22:1, 24:1, 26:1, 30:1, 32:1, 34:1, 36:1, or 40:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, and more preferably it is (8:1) to (20:1).

[0012] Furthermore, the mass ratio of the metal oxide to the molecular sieve in the core layer of the catalyst is (1:10) to (10:1), for example, it can be 1:10, 1:9, 1:8, 1:7, 1:6, 1:5, 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 or 10:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, and more preferably (1:3) to (3:1).

[0013] Further, the metal element in the metal oxide component of the catalyst is selected from one or more of Cr, Mn, Zr, La, Ce, Al, Ti, Zn, In and Ga, preferably one or more of Cr, Zr, Al, Zn, In, Ga, more preferably one or more of Zn-Cr, Zn-Al, Zn-Zr, In-Zr, Ga-Zr, Zn-Cr-Al, Zn-Ga-Zr, Zn-In-Zr, Ga-In-Zr combination. In the present invention, the synergistic effect between the above metals can promote the activation and hydrogenation reaction of CO2 and improve the CO2 conversion rate.

[0014] Furthermore, the molecular sieve in the catalyst is selected from one or more of ZSM-5, ZSM-11, Silicalite-1, Silicalite-2, Beta, MOR, and USY, preferably one or more of ZSM-5, ZSM-11, Silicalite-1, and Silicalite-2, and more preferably one or more of ZSM-5 and Silicalite-1.

[0015] According to a preferred embodiment of the present invention, the metal oxide in the catalyst is Cr2O3, the molecular sieve is ZSM-5, and the silicon dioxide is used as the shell layer, and is used in the one-step hydrogenation of CO2 to aromatics, achieving outstanding technical effects. Further preferably, the catalyst consists only of the above ingredients.

[0016] According to a preferred embodiment of the present invention, the metal oxide in the catalyst is an In-Zr composite oxide, the molecular sieve is ZSM-5, and the silicon dioxide is used as the shell layer, and is used in the one-step hydrogenation of CO2 to aromatics, achieving outstanding technical effects. Further preferably, the catalyst consists only of the above ingredients.

[0017] According to a preferred embodiment of the present invention, the metal oxide in the catalyst is Zn-Cr composite oxide, the molecular sieve is ZSM-5, and the silicon dioxide is used as the shell layer, and is used in the one-step hydrogenation of CO2 to aromatics, achieving outstanding technical effects. Further preferably, the catalyst consists only of the above ingredients.

[0018] The second aspect of the present invention provides a method for preparing the above catalyst, comprising the following steps:

[0019] (1) mixing a metal salt solution and a precipitant solution, and aging them to obtain a metal precipitate;

[0020] (2) dispersing the metal precipitate and the optional molecular sieve of step (1) in an alcohol solution, adjusting the pH of the dispersion system to 6 to 8, and performing hydrothermal treatment to obtain a precursor dispersion liquid I;

[0021] (3) Optionally, adding molecular sieves to the precursor dispersion I of step (2) to obtain a precursor dispersion II;

[0022] (4) mixing the precursor dispersion liquid I and / or the precursor dispersion liquid II with the silicon-containing modified solution, aging, and calcining to obtain a catalyst;

[0023] Wherein, the molecular sieve is added in step (2) and / or step (3).

[0024] Furthermore, the metal salt in step (1) is at least one of metal nitrate, metal acetate, metal carbonate and metal chloride. Furthermore, the precipitant in step (1) is at least one of ammonia water, ammonium carbonate, potassium carbonate, sodium carbonate, potassium hydroxide and sodium hydroxide.

[0025] Furthermore, based on the theoretical amount of the precipitant required for complete precipitation of the metal cation as 1, the mixing ratio of the metal salt and the precipitant in step (1) is 0.5 to 1.5, preferably 0.9 to 1.2.

[0026] In the present invention, the mass concentration of the metal salt solution in step (1) is 5% to 70%, and the mass of the metal salt is the mass of the solute. In the present invention, the mass concentration of the precipitant solution in step (1) is 2% to 30%, and the mass of the precipitant is the mass of the solute.

[0027] Furthermore, the metal salt solution and the precipitant solution in step (1) are mixed by conventional methods in the art, preferably by co-current precipitation of the metal salt solution and the precipitant solution.

[0028] Furthermore, the aging treatment in step (1) is carried out at 50 to 80° C. for 1 to 24 hours.

[0029] Furthermore, step (1) further comprises: after the aging treatment, optionally filtering, optionally washing, optionally filtering, and optionally drying to obtain a metal precipitate. The present invention has no limitation on the conditions of filtering, washing, filtering, and drying, and those skilled in the art can freely choose.

[0030] Furthermore, in step (2), the metal precipitate and the optional molecular sieve are dispersed in an alcohol solution, wherein the liquid-solid mass ratio is 4 to 30: 1. The volume ratio of the solvent to the alcohol in the alcohol solution is (1:10) to (50:1), and the solvent is preferably water.

[0031] Furthermore, the alcohol in step (2) is selected from one or more of ethanol, propanol, isopropanol, butanol and isobutanol.

[0032] Furthermore, the method for adjusting the pH of the dispersed system in step (2) can adopt conventional methods in the art without any limitation, such as adding one or more of ammonia water, urea, acetic acid, hydrochloric acid, phosphate buffer solution, etc. to adjust the pH of the dispersed system.

[0033] Furthermore, in the present invention, the hydrothermal treatment in step (2) is to enrich the surface of the metal precipitate with hydroxyl groups so that it can be fully eliminated as a silicon dioxide deposition site in the subsequent steps.

[0034] Furthermore, in step (2), the hydrothermal treatment condition is 90-120° C. for 2-20 h.

[0035] Furthermore, based on the metal in the precursor dispersion I as oxide, the mass ratio of the molecular sieve added in step (2) and / or step (3) to the metal oxide is (1:10) to (10:1).

[0036] Furthermore, the silicon-containing modified solution in step (4) is a mixture of a silicon-containing modifier and an organic solvent.

[0037] Furthermore, in step (4), the silicon-containing modifier is at least one of silica sol, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, and ethyltriethoxysilane.

[0038] Furthermore, in step (4), the organic solvent is at least one of n-hexane, cyclohexane, n-heptane and n-octane.

[0039] Furthermore, in step (4), the volume ratio of the silicon-containing modifier to the organic solvent is (1:10) to (1:1).

[0040] Furthermore, in step (4), the volume ratio of the precursor dispersion liquid I and / or the precursor dispersion liquid II to the silicon-containing modified solution is (1:4) to (4:1).

[0041] According to a preferred embodiment of the present invention, a surfactant is added in the step of mixing the precursor dispersion I and / or the precursor dispersion II with the silicon-containing modified solution in step (4). Preferably, the precursor dispersion I and / or the precursor dispersion II are mixed with the surfactant and then mixed with the silicon-containing modified solution.

[0042] Furthermore, in step (4), the mass ratio of the catalyst contained in the precursor dispersion I and / or the precursor dispersion II to the surfactant is (10:1) to (50:1).

[0043] Furthermore, the surfactant in step (4) is at least one of alkyltrimethylammonium salts, dialkyldimethylammonium salts, and alkyldimethylbenzylammonium salts, preferably at least one of tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride, dimethyldiallylammonium bromide, and dimethyldiallylammonium chloride.

[0044] Furthermore, the aging treatment in step (4) is carried out at 20-70°C for 12-48 hours, and the calcination is carried out at 400-600°C for 2-6 hours.

[0045] Furthermore, after the aging in step (4), the product is dried. In the present invention, drying is mainly to remove moisture on the surface of the mixed material, to ensure the quality of the obtained catalyst material and to improve the stability of the material. Conventional drying methods can be used. Preferably, the drying is vacuum drying.

[0046] The third aspect of the present invention provides the use of the above-mentioned catalyst in the one-step hydrogenation of CO2 to aromatics, wherein the catalyst is the catalyst provided in the first aspect or the catalyst prepared by the preparation method provided in the second aspect.

[0047] Furthermore, the application includes: using CO2 / H2 as raw material, contacting the raw material with the catalyst to react, and obtaining a flow containing hydrocarbon products.

[0048] Furthermore, the H2 / CO2 molar ratio in the raw gas is 2.0 to 6.0; preferably, the H2 / CO2 molar ratio is 2.5 to 4.0.

[0049] Furthermore, the reaction conditions are: reaction temperature 300-550°C; and / or reaction pressure 1.0-8.0 MPa; and / or volume space velocity 600-10000 h -1 .

[0050] In the reaction system of CO2 one-step hydrogenation to hydrocarbons based on metal oxide-molecular sieve coupling catalysis for methanol synthesis, CO2 and H2 first undergo hydrogenation reaction on the surface of metal oxide to generate methanol intermediates, which diffuse and transfer from the surface of metal oxide to the molecular sieve, and then undergo further aromatization reaction to generate aromatics. The aromatization reaction of methanol intermediates is a multi-molecular reaction. The higher concentration of methanol intermediates in the molecular sieve pores is conducive to the occurrence of aromatization reaction. Therefore, the close contact between metal oxide and molecular sieve components is conducive to the rapid migration of methanol intermediates, which helps to improve the CO2 conversion rate and aromatics selectivity of this system. In addition, reverse water gas shift (RWGS) reaction will occur on the surface of metal oxide, which is one of the main side reactions of this system. This side reaction generates CO and H2O from CO2 and H2, reducing the utilization rate of hydrogen and carbon atoms. How to suppress RWGS reaction and improve aromatics selectivity at a higher CO2 conversion rate, thereby improving hydrogen-carbon conversion efficiency and atom economy, is a problem that needs to be solved by the present invention.

[0051] By adopting the technical scheme of the present invention, through the surface modification of the metal oxide and molecular sieve combined catalyst, it is applied to the one-step hydrogenation of CO2 to aromatics reaction, the CO selectivity is reduced to below 50%, the organic product selectivity and aromatics yield, and the utilization rate of hydrogen and carbon atoms are greatly improved, and good technical effects are achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 are infrared spectra of ZSM-5 (100), catalysts of Example 1 and Comparative Example 1;

[0053] in, Figure 1 Wherein (1) is ZSM-5 (100) prepared in Example 1, (2) and (3) are catalysts of Comparative Example 1 and Example 1, respectively;

[0054] Of which 3696cm -1 、3657cm -1 、3628cm -1 and 3596cm -1 Nearby is the characteristic peak of hydroxyl group bonded to chromium; 3740cm -1 Nearby is the characteristic peak of silanol; 3610cm -1 Nearby is the characteristic peak of silicon-aluminum bridged hydroxyl. Among them, (1) and (2) have been calculated according to the characteristic peak of ZSM-5 molecular sieve framework (1500-2000cm -1 ) intensity, (2) and (3) have been calibrated according to the chromium-oxygen vibration peak intensity of chromium oxide. DETAILED DESCRIPTION

[0055] The following examples will further illustrate the technical solutions provided by the present invention, but the protection scope of the present invention is not limited by these examples.

[0056] In the present invention, the infrared test is carried out on a NICOLET 5700 infrared spectrometer equipped with an in-situ cell. An appropriate amount of sample is weighed and pressed into a self-supporting sheet, which is placed in an infrared cell with CaF2 as a window. The sample is treated at 400°C for 2 hours under high vacuum, and then cooled to 200°C to collect the spectrum.

[0057] In the present invention, the post-reaction logistics includes unconverted CO2 and H2, as well as hydrocarbon products, which are C6~C 10+ Aromatics and / or C1~C 5+ Hydrocarbon composition. The selectivity of each product is defined as the proportion of each product in the total carbon number of the organic product (mol%). The specific calculation method is as follows:

[0058] CO2 conversion rate = CO2 conversion amount / CO2 feed amount × 100%,

[0059] CO selectivity = CO production / CO2 conversion × 100%,

[0060] Total carbon number of organic products = Σ(amount of substance of organic product i × number of carbon atoms in organic product i molecule),

[0061] Selectivity of organic product j = amount of substance of organic product j × number of carbon atoms in organic product j molecule / total carbon number of organic product × 100%,

[0062] Aromatic selectivity = C6 aromatic selectivity + C7 aromatic selectivity + C8 aromatic selectivity + C9 aromatic selectivity + C 10+ Aromatic selectivity,

[0063] Aromatic hydrocarbon yield = CO2 conversion rate × (1-CO selectivity) × aromatic hydrocarbon selectivity × 100%.

[0064] [Example 1]

[0065] Cr2O3 was prepared by precipitation method. 52.66g chromium nitrate was dissolved in 70mL deionized water, and 19.91g ammonium carbonate was dissolved in 94.0mL deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added to 10mL deionized water at a drop rate of 5mL / min and 6.7mL / min, respectively. After precipitation, the mother liquor was aged in a 70℃ constant temperature water bath for 3h, filtered, and washed with deionized water until neutral. The obtained metal precipitate was dispersed in an ethanol solution of 5 times its mass (the volume ratio of water to ethanol in the solution was 1:1), and its pH value was adjusted to 7. It was hydrothermally treated at 105℃ for 10h to obtain a Cr2O3 precursor dispersion. ZSM-5 molecular sieve with Si / Al molar ratio = 100 was synthesized by hydrothermal method, recorded as ZSM-5 (100). Based on the Cr2O3 in the Cr2O3 precursor dispersion, 10.0 g of ZSM-5 (100) was added to the Cr2O3 precursor dispersion and fully mixed according to the mass ratio of Cr2O3 to ZSM-5 (100) of 1:1 to obtain a catalyst precursor dispersion. 13.88 g of tetraethyl orthosilicate was dissolved in 24 mL of n-hexane and fully mixed with the catalyst precursor dispersion, aged at 25°C for 24 h, vacuum dried at 80°C, and calcined at 500°C for 4 h to obtain a core-shell structure catalyst with SiO2 as the shell layer, wherein the mass ratio of the combined catalyst of the core layer to the SiO2 of the shell layer was 5.0, recorded as [Cr2O3 / ZSM-5 (100) (1:1)]@SiO2 (5.0).

[0066] The surface hydroxyl groups of ZSM-5(100) and [Cr2O3 / ZSM-5(100)(1:1)]@SiO2(5.0) were characterized by infrared spectroscopy. Figure 1 (1) and (3). In ZSM-5(100), an infrared absorption peak was detected at 3610 cm -1 Nearby silicon-aluminum bridged hydroxyl groups, and 3740 cm -1 In the infrared spectrum of [Cr2O3 / ZSM-5(100)(1:1)]SiO2(5.0), in addition to basically retaining the basic characteristic peaks of ZSM-5(100), the characteristic peaks of silanol are significantly enhanced, and the intensity of the characteristic peaks of hydroxyl groups bonded to chromium is greatly weakened.

[0067] The obtained core-shell catalyst was pelletized and loaded into a reactor, and a H2 / CO2 mixed gas with a molar ratio of 3.0 was used as a raw material at a space velocity of 1200 h -1The reaction was carried out under the conditions of 350°C, 4.0MPa and temperature. The catalyst was pretreated with H2 for 2h at 380°C before the reaction. The results of the metal hydroxyl content in the catalyst (based on the metal hydroxyl characteristic peak area / content in the infrared spectrum of the catalyst without the encapsulating shell layer in Comparative Example 1, i.e., 1) and the relative content of silanol / metal hydroxyl, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0068] [Example 2]

[0069] The method of Example 1 was followed, except that the mass ratio of the core layer catalyst to the shell layer SiO2 was 10.0. The obtained core-shell structure catalyst was recorded as [Cr2O3 / ZSM-5(100)(1:1)]@SiO2(10.0).

[0070] [Example 3]

[0071] The method of Example 1 is followed, except that: in the core layer catalyst, the metal oxide is a Zn-Cr oxide with a Zn / Cr molar ratio of 1 / 2, which is recorded as 1Zn-2Cr. The preparation method of the 1Zn-2Cr precipitate adopts a precipitation method, dissolving 7.89g of zinc acetate and 34.41g of chromium nitrate in 75mL of deionized water, diluting 70.0g of ammonia water (concentration 25wt%) with 47.5mL of deionized water, and under strong stirring, adding the metal salt solution and the precipitant solution to 15mL of deionized water at a drop rate of 3.75mL / min and 5mL / min respectively. After the precipitation is completed, the mother liquor is aged in a constant temperature water bath at 50°C for 24h, and then filtered without additional washing. The obtained core-shell structure catalyst is recorded as [1Zn-2Cr / ZSM-5(100)(1:1)]@SiO2(5.0).

[0072] [Example 4]

[0073] According to the method of Example 1, the difference is that: in the core layer catalyst, the metal oxide is an In-Zr oxide with an In / Zr molar ratio of 1 / 6, which is recorded as 1In-6Zr. The preparation method of the 1In-6Zr precipitate adopts a precipitation method, dissolving 4.36g of indium nitrate and 29.39g of zirconium nitrate in 600mL of deionized water, dissolving 11.09g of sodium hydroxide in 420.0mL of deionized water, and under strong stirring, the metal salt solution and the precipitant solution are added to 30mL of deionized water at a drop rate of 10mL / min and 7mL / min respectively. After the precipitation is completed, the mother liquor is aged in a constant temperature water bath at 80°C for 1h, and then filtered and washed with deionized water until neutral. The obtained core-shell structure catalyst is recorded as [1In-6Zr / ZSM-5(100)(1:1)]@SiO2(5.0).

[0074] [Example 5]

[0075] The Zn-Cr oxide with a Zn / Cr molar ratio of 2 / 1 was prepared by precipitation method, denoted as 2Zn-1Cr. 12.50g zinc nitrate and 8.40g chromium nitrate were dissolved in 40mL deionized water, 9.0g potassium hydroxide was dissolved in 30mL deionized water, and the metal salt solution and the precipitant solution were added to 5mL deionized water at a drop rate of 0.67mL / min and 0.5mL / min respectively under strong stirring. After precipitation, the mother liquor was aged in a 60℃ constant temperature water bath for 5h, filtered, and washed with deionized water until neutral. The obtained metal precipitate was dispersed in an ethanol solution of 25 times its mass (the volume ratio of water to ethanol in the solution was 2:1), and its pH value was adjusted to 7.5. It was hydrothermally treated at 90℃ for 8h to obtain a 2Zn-1Cr precursor dispersion. The ZSM-5 molecular sieve with Si / Al molar ratio = 200 was synthesized by hydrothermal method, denoted as ZSM-5 (200). Based on the 2Zn-1Cr oxide in the 2Zn-1Cr precursor dispersion, 50.0 g of ZSM-5 (200) was added to the 2Zn-1Cr precursor dispersion at a mass ratio of 2Zn-1Cr to ZSM-5 (200) of 1:10 and the mixture was fully mixed to obtain a catalyst precursor dispersion. 4.77g of tetraethyl orthosilicate was dissolved in 40mL of n-hexane and fully mixed with the catalyst precursor dispersion, aged at 40°C for 18h, vacuum dried at 80°C, and calcined at 480°C for 5h to obtain a core-shell catalyst with a shell layer of SiO2, wherein the metal oxide in the core layer catalyst is 2Zn-1Cr, the molecular sieve is ZSM-5(200), and the mass ratio of the metal oxide to the molecular sieve in the core layer is 1:10; the mass ratio of the core layer catalyst to the shell layer SiO2 is 40.0, and the obtained core-shell catalyst is recorded as [2Zn-1Cr / ZSM-5(200)(1:10)]@SiO2(40.0). The core-shell catalyst was pressed into tablets and granulated, and then loaded into a reactor. A H2 / CO2 mixed gas with a molar ratio of 3.5 was used as a raw material at a space velocity of 800h -1 The reaction was carried out under the conditions of 320°C, 7.0 MPa, and 380°C for 2 h.

[0076] [Example 6]

[0077] ZrO2 was prepared by precipitation method. 174.52g zirconium nitrate was dissolved in 2000mL deionized water, and 90.49g sodium carbonate was dissolved in 1000mL deionized water. Under strong stirring, the metal salt solution and the precipitant solution were added to 100mL deionized water at a drop rate of 50mL / min and 25mL / min, respectively. After precipitation, the mother liquor was aged in a 70℃ constant temperature water bath for 10h, filtered, and washed with deionized water until neutral. The obtained metal precipitate was dispersed in a butanol solution with a mass of 10 times (the volume ratio of water to butanol in the solution was 1:10), and its pH value was adjusted to 8. It was hydrothermally treated at 120℃ for 18h to obtain a ZrO2 precursor dispersion. ZSM-5 molecular sieve with Si / Al molar ratio = 30 was synthesized by hydrothermal method, recorded as ZSM-5 (30). Based on the ZrO2 in the ZrO2 precursor dispersion, the mass ratio of ZrO2 to ZSM-5(30) was 10:1, and 5.0 g of ZSM-5(30) was added to the ZrO2 precursor dispersion and fully mixed to obtain a catalyst precursor dispersion. 47.67 g of tetraethyl orthosilicate was dissolved in 200 mL of n-hexane, and fully mixed with the catalyst precursor dispersion, aged at 30°C for 20 h, vacuum dried at 90°C, and calcined at 550°C for 3 h to obtain a core-shell catalyst with a shell layer of SiO2, wherein the metal oxide in the core layer catalyst is ZrO2, the molecular sieve is ZSM-5(30), and the mass ratio of the metal oxide to the molecular sieve in the core layer is 10:1; the mass ratio of the core layer catalyst to the shell layer SiO2 is 4.0, and the obtained core-shell catalyst is recorded as [ZrO2 / ZSM-5(30)(10:1)]@SiO2(4.0).

[0078] [Example 7]

[0079] The method of Example 3 is followed, except that: in the core layer catalyst, the molecular sieves are ZSM-5 (100) and ZSM-11 (100) in a mass ratio of 2 / 1. The obtained core-shell structure catalyst is recorded as [1Zn-2Cr / ZSM-5 (100) & ZSM-11 (100) (1:1)]@SiO2 (5.0).

[0080] [Example 8]

[0081] The method of Example 3 is different in that: the preparation method of the 1Zn-2Cr precursor dispersion is that the metal precipitate is dispersed in an isopropanol solution of 4 times its mass (the volume ratio of water to isopropanol in the solution is 45:1), the pH value is adjusted to 6.0, and the 1Zn-2Cr precursor dispersion is obtained by hydrothermal treatment at 110°C for 20h. The obtained core-shell structure catalyst is recorded as [1Zn-2Cr(IPA) / ZSM-5(100)(1:1)]@SiO2(5.0).

[0082] [Example 9]

[0083] The method of Example 3 is the same, except that: the introduction method of the shell layer containing SiO2 is to dissolve 10.14g of methyl orthosilicate in 30mL of cyclohexane, and fully mix it with the combined catalyst precursor dispersion, age it at room temperature for 24h, vacuum dry it at 80°C, and calcine it at 500°C for 4h to obtain a core-shell catalyst containing SiO2 on the surface. The obtained core-shell catalyst is recorded as [1Zn-2Cr / ZSM-5(100)(1:1)]@SiO2(TMOS,5.0).

[0084] [Example 10]

[0085] The method of Example 4 is followed, except that: based on the theoretical mass of the catalyst contained in the catalyst precursor dispersion, the surfactant hexadecyltrimethylammonium bromide is added to the catalyst precursor dispersion at a mass ratio of 50:1, and then mixed with the silicon-containing modified solution. The obtained core-shell structure catalyst is recorded as [1In-6Zr / ZSM-5(100)(CTAB,1:1)]@SiO2(5.0).

[0086] [Example 11]

[0087] The method of Example 4 was followed, except that: based on the theoretical mass of the catalyst contained in the catalyst precursor dispersion, the surfactant dimethyldiallyl ammonium chloride was added to the catalyst precursor dispersion at a mass ratio of 10:1, and then mixed with the silicon-containing modified solution. The resulting core-shell structure catalyst was recorded as [1In-6Zr / ZSM-5(100)(DMDAAC,1:1)]@SiO2(5.0).

[0088] [Comparative Example 1]

[0089] Cr2O3 was prepared by precipitation method. 52.66g of chromium nitrate was dissolved in 70mL of deionized water, and 19.91g of ammonium carbonate was dissolved in 94.0mL of deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added dropwise to 10mL of deionized water at a dropping rate of 5mL / min and 6.7mL / min, respectively. After precipitation, the mother liquor was aged in a 70℃ constant temperature water bath for 3h, then filtered, washed with deionized water until neutral, vacuum dried at 80℃, and calcined at 500℃ for 4h to obtain Cr2O3.

[0090] Cr2O3 and ZSM-5 (100) (same as in Example 1) were mixed in a mass ratio of 1:1 to obtain a catalyst. The surface hydroxyl groups of the catalyst were characterized by infrared spectroscopy. Figure 1In the Cr2O3 / ZSM-5(100) catalyst, in addition to retaining the characteristic peaks of silanol bridged hydroxyl and silanol of ZSM-5(100), the peak at 3696 cm -1 、3657cm -1 、3628cm -1 、3596cm -1 A strong characteristic peak of hydroxyl group bonded to chromium was detected near the catalyst. The catalyst was pressed into tablets and granulated and loaded into the reactor. A H2 / CO2 mixed gas with a molar ratio of 3.0 was used as the raw material at a space velocity of 1200h -1 The reaction was carried out under the conditions of 350°C, 4.0 MPa. The catalyst was pretreated with H2 at 380°C for 2 h before the reaction. The results of the metal hydroxyl content, the relative content of silanol / metal hydroxyl in the catalyst, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0091] [Comparative Example 2]

[0092] Cr2O3 was prepared by precipitation method. 52.66g of chromium nitrate was dissolved in 70mL of deionized water, and 19.91g of ammonium carbonate was dissolved in 94.0mL of deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added to 10mL of deionized water at a dropping rate of 5mL / min and 6.7mL / min respectively. After precipitation, the mother liquor was aged in a 70°C constant temperature water bath for 3h, filtered, washed with deionized water until neutral, vacuum dried at 80°C, and roasted at 700°C for 10h to obtain Cr2O3. High temperature and long-term roasting can remove some hydroxyl groups contained in Cr2O3. Cr2O3-700 and ZSM-5 (100) (same as Example 1) were fully mixed in a mass ratio of 1:1 to obtain a combined catalyst. The combined catalyst was loaded into a reactor after tabletting and granulation, and a H2 / CO2 mixed gas with a molar ratio of 3.0 was used as a raw material at an air velocity of 1200h. -1 The reaction was carried out under the conditions of 350°C, 4.0 MPa. The catalyst was pretreated with H2 at 380°C for 2 h before the reaction. The results of the metal hydroxyl content, the relative content of silanol / metal hydroxyl in the catalyst, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0093] [Comparative Example 3]

[0094] Cr2O3 was prepared by precipitation method. 52.66g of chromium nitrate was dissolved in 70mL of deionized water, and 19.91g of ammonium carbonate was dissolved in 94.0mL of deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added dropwise in parallel into 10mL of deionized water at a dropping speed of 5mL / min and 6.7mL / min, respectively. After precipitation, the mother liquor was aged in a constant temperature water bath at 70℃ for 3h, filtered, and washed with deionized water until neutral. The filter cake was dispersed in a mixed solution of deionized water and ethanol (the volume ratio of water to ethanol was 1:1) with a mass of 5 times that of the mixed solution, and its pH value was adjusted to 7. The mixture was hydrothermally treated at 105℃ for 10h to obtain a Cr2O3 precursor dispersion. 6.94 g of tetraethyl orthosilicate was dissolved in 24 mL of n-hexane and fully mixed with the Cr2O3 precursor dispersion, aged at 30°C for 24 h, vacuum dried at 80°C, and calcined at 500°C for 4 h to obtain a modified Cr2O3 with a shell layer of SiO2, wherein the mass ratio of Cr2O3 to SiO2 was 5.0, recorded as Cr2O3-SiO2 (5.0). A ZSM-5 molecular sieve with a Si / Al molar ratio of 100 was synthesized by hydrothermal method, recorded as ZSM-5 (100) (same as Example 1). 6.94 g of tetraethyl orthosilicate was dissolved in 24 mL of n-hexane, 10.0 g of ZSM-5 (100) was added thereto and mixed thoroughly, aged at 30°C for 24 h, vacuum dried at 80°C, and calcined at 500°C for 4 h to obtain modified ZSM-5 (100) with a SiO2 shell, wherein the mass ratio of ZSM-5 (100) to SiO2 was 5.0, recorded as ZSM-5 (100) -SiO2 (5.0).

[0095] The catalyst was obtained by mixing Cr2O3-SiO2(5.0) and ZSM-5(100)-SiO2(5.0) in a mass ratio of 1:1. The catalyst was pelletized and loaded into a reactor. A H2 / CO2 mixed gas with a molar ratio of 3.0 was used as the raw material at a space velocity of 1200 h -1 The reaction was carried out under the conditions of 350°C, 4.0 MPa. The catalyst was pretreated with H2 at 380°C for 2 h before the reaction. The results of the metal hydroxyl content, the relative content of silanol / metal hydroxyl in the catalyst, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0096] [Comparative Example 4]

[0097] Cr2O3 was prepared by precipitation method. 52.66g of chromium nitrate was dissolved in 70mL of deionized water, and 19.91g of ammonium carbonate was dissolved in 94.0mL of deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added dropwise to 10mL of deionized water at a dropping rate of 5mL / min and 6.7mL / min, respectively. After precipitation, the mother liquor was aged in a 70°C constant temperature water bath for 3h, then filtered, washed with deionized water until neutral, vacuum dried at 80°C, and calcined at 500°C for 4h to obtain Cr2O3. A ZSM-5 molecular sieve with a Si / Al molar ratio of 100 was synthesized by hydrothermal method, recorded as ZSM-5 (100) (same as Example 1). Dissolve 6.94g of tetraethyl orthosilicate in 24mL of n-hexane, add 10.0g of ZSM-5(100) and mix thoroughly, age at 30℃ for 24h, vacuum dry at 80℃, and calcine at 500℃ for 4h to obtain modified ZSM-5(100) with SiO2 as the shell, where the mass ratio of ZSM-5(100) to SiO2 is 5.0, recorded as ZSM-5(100)-SiO2(5.0). Mix Cr2O3 and ZSM-5(100)-SiO2(5.0) in a mass ratio of 1:1 to obtain a catalyst. After tabletting and granulation, the catalyst is loaded into a reactor, and a H2 / CO2 mixed gas with a molar ratio of 3.0 is used as the raw material at a space velocity of 1200h -1 The reaction was carried out under the conditions of 350°C, 4.0 MPa. The catalyst was pretreated with H2 at 380°C for 2 h before the reaction. The results of the metal hydroxyl content, the relative content of silanol / metal hydroxyl in the catalyst, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0098] [Comparative Example 5]

[0099] Cr2O3 was prepared by precipitation method: 52.66g of chromium nitrate was dissolved in 70mL of deionized water, and 19.91g of ammonium carbonate was dissolved in 94.0mL of deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added dropwise in parallel into 10mL of deionized water at a dropping speed of 5mL / min and 6.7mL / min, respectively. After precipitation, the mother liquor was aged in a constant temperature water bath at 70°C for 3h, then filtered and washed with deionized water until neutral. The filter cake was dispersed in a mixed solution of deionized water and ethanol with a mass of 5 times (the volume ratio of water to ethanol was 1:1), the pH value was adjusted to 7, and hydrothermally treated at 105°C for 10h to obtain a Cr2O3 precursor dispersion. 6.94 g of tetraethyl orthosilicate was dissolved in 24 mL of n-hexane and fully mixed with the Cr2O3 precursor dispersion, aged at 30°C for 24 h, vacuum dried at 80°C, and calcined at 500°C for 4 h to obtain a modified Cr2O3 with a shell of SiO2, wherein the mass ratio of Cr2O3 to SiO2 was 5.0, recorded as Cr2O3-SiO2 (5.0). Cr2O3-SiO2 (5.0) and ZSM-5 (100) (same as Example 1) were fully mixed at a mass ratio of 1:1 to obtain a catalyst. The catalyst was tableted and granulated and loaded into a reactor, and a H2 / CO2 mixed gas with a molar ratio of 3.0 was used as a raw material at an air velocity of 1200 h -1 The reaction was carried out under the conditions of 350°C, 4.0 MPa. The catalyst was pretreated with H2 at 380°C for 2 h before the reaction. The results of the metal hydroxyl content, the relative content of silanol / metal hydroxyl in the catalyst, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0100] [Comparative Example 6]

[0101] Cr2O3 was prepared by precipitation method. 52.66g chromium nitrate was dissolved in 70mL deionized water, and 19.91g ammonium carbonate was dissolved in 94.0mL deionized water. Under strong stirring, the chromium nitrate solution and the ammonium carbonate solution were added to 10mL deionized water at a drop rate of 5mL / min and 6.7mL / min, respectively. After precipitation, the mother liquor was aged in a 70℃ constant temperature water bath for 3h, filtered, and washed with deionized water until neutral. The obtained metal precipitate was dispersed in an ethanol solution of 5 times its mass (the volume ratio of water to ethanol in the solution was 1:1), and the pH value was adjusted to 7 to obtain a Cr2O3 precursor dispersion. ZSM-5 molecular sieve with Si / Al molar ratio = 100 was synthesized by hydrothermal method, recorded as ZSM-5 (100). Based on the Cr2O3 in the Cr2O3 precursor dispersion, the mass ratio of Cr2O3 to ZSM-5(100) was 1:1, and 10.0 g of ZSM-5(100) was added to the Cr2O3 precursor dispersion and fully mixed to obtain a catalyst precursor dispersion. 13.88 g of tetraethyl orthosilicate was dissolved in 24 mL of n-hexane and fully mixed with the catalyst precursor dispersion, aged at 25°C for 24 h, vacuum dried at 80°C, and calcined at 500°C for 4 h to obtain a core-shell catalyst with a shell layer of SiO2, wherein the mass ratio of the combined catalyst of the core layer to the SiO2 of the shell layer was 5.0, recorded as [Cr2O3 / ZSM-5(100)(without hydrothermal, 1:1)]@SiO2(5.0).

[0102] The obtained core-shell catalyst was pelletized and loaded into a reactor, and a H2 / CO2 mixed gas with a molar ratio of 3.0 was used as a raw material at a space velocity of 1200 h -1 The reaction was carried out under the conditions of 350°C, 4.0 MPa. The catalyst was pretreated with H2 at 380°C for 2 h before the reaction. The results of the metal hydroxyl content, the relative content of silanol / metal hydroxyl in the catalyst, CO2 conversion, CO selectivity, aromatics selectivity and aromatics yield are shown in Table 1.

[0103] Table 1

[0104]

[0105]

[0106] It can be seen from the results in Table 1 that the catalyst provided by the present invention can inhibit the reverse water gas shift reaction. Compared with the existing oxide-molecular sieve catalysts without surface treatment, or catalysts with surface treatment of oxides or molecular sieves alone, it has the outstanding technical effects of significantly reducing CO selectivity and improving aromatics yield.

[0107] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for one-step hydrogenation of CO2 to aromatics, the catalyst having a core-shell structure, comprising a core layer containing at least a metal oxide and a molecular sieve and a shell layer of silicon dioxide.

2. The catalyst according to claim 1, characterized in that Taking the characteristic absorption peak area of ​​metal hydroxyl group in the infrared spectrum of the catalyst having only a core layer but no shell layer as 1, the absorption peak area of ​​metal hydroxyl group in the infrared spectrum of the catalyst is less than 0.

1.

3. The catalyst according to claim 1, characterized in that Calculated by the area ratio of the characteristic absorption peak of silanol group to the characteristic absorption peak of metal hydroxyl group in the infrared spectrum of the catalyst, the relative content of silanol group / metal hydroxyl group of the catalyst is 4.0-10.

0.

4. The catalyst according to claim 1, characterized in that The mass ratio of the core layer to the shell layer in the catalyst is (4:1) to (40:1); the mass ratio of the metal oxide to the molecular sieve in the core layer of the catalyst is (1:10) to (10:1).

5. The catalyst according to claim 1, characterized in that The metal element in the metal oxide component of the catalyst is selected from one or more of Cr, Mn, Zr, La, Ce, Al, Ti, Zn, In and Ga; the molecular sieve in the catalyst is selected from one or more of ZSM-5, ZSM-11, Silicalite-1, Silicalite-2, Beta, MOR, USY.

6. A method for preparing a catalyst according to any one of claims 1 to 5, comprising the following steps: (1) mixing a metal salt solution and a precipitant solution, and aging them to obtain a metal precipitate; (2) dispersing the metal precipitate and the optional molecular sieve of step (1) in an alcohol solution, adjusting the pH of the dispersion system to 6 to 8, and performing hydrothermal treatment to obtain a precursor dispersion liquid I; (3) Optionally, adding molecular sieves to the precursor dispersion I of step (2) to obtain a precursor dispersion II; (4) mixing the precursor dispersion liquid I and / or the precursor dispersion liquid II with the silicon-containing modified solution, aging, and calcining to obtain a catalyst; Wherein, the molecular sieve is added in step (2) and / or step (3).

7. The preparation method according to claim 6, characterized in that: The metal salt in step (1) is at least one of metal nitrate, metal acetate, metal carbonate and metal chloride; the precipitant is at least one of ammonia water, ammonium carbonate, potassium carbonate, sodium carbonate, potassium hydroxide and sodium hydroxide.

8. The preparation method according to claim 6, characterized in that: The aging treatment in step (1) is carried out at 50 to 80° C. for 1 to 24 hours.

9. The preparation method according to claim 6, characterized in that: In step (2), the metal precipitate and the optional molecular sieve are dispersed in an alcohol solution, wherein the liquid-to-solid mass ratio is 4 to 30:1; wherein the volume ratio of the solvent to the alcohol in the alcohol solution is (1:10) to (50:1); the alcohol in step (2) is selected from one or more of ethanol, propanol, isopropanol, butanol, and isobutanol.

10. The preparation method according to claim 6, characterized in that: The hydrothermal treatment conditions in step (2) are 90-120° C. for 2-20 hours.

11. The preparation method according to claim 6, characterized in that: Calculated as oxides of the metal in the precursor dispersion I, the mass ratio of the molecular sieve added in step (2) and / or step (3) to the metal oxide is (1:10) to (10:1).

12. The preparation method according to claim 6, characterized in that: The silicon-containing modifier in step (4) is at least one of silica sol, methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate, butyl orthosilicate, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, and ethyltriethoxysilane; the organic solvent in step (4) is at least one of n-hexane, cyclohexane, n-heptane, and n-octane; the surfactant in step (4) is at least one of alkyltrimethylammonium salt, dialkyldimethylammonium salt, and alkyldimethylbenzylammonium salt.

13. The preparation method according to claim 6, characterized in that: The aging treatment in step (4) is carried out at 20-70°C for 12-48 hours. The calcination is carried out at 400-600°C for 2-6 hours.

14. Use of the catalyst according to any one of claims 1 to 5 in one-step hydrogenation of CO2 to aromatics.

15. The use according to claim 14, characterized in that: The application includes: using CO2 / H2 as raw materials, contacting the raw materials with the catalyst for reaction, and obtaining a logistics containing hydrocarbon products; preferably, the H2 / CO2 molar ratio in the raw gas is 2.0-6.0; preferably, the reaction conditions are: reaction temperature 300-550°C; and / or reaction pressure 1.0-8.0MPa; and / or volume space velocity 600-10000h -1 .

Citation Information

Patent Citations

  • Method for preparing aromatic hydrocarbons through hydrogenation of carbon dioxide

    CN107840778A

  • Catalyst for synthesizing aromatic hydrocarbon and preparation method and application of catalyst

    CN110496639A

  • ZSM-5 composite molecular sieve with a core-shell structure and preparation method and application thereof

    CN103803581A

  • Low-CO2-selectivity core-shell catalyst for alkene preparation through CO hydrogenation and preparation method of catalyst

    CN107694607A

  • Core-shell structure multifunctional catalyst system and application thereof

    CN109701604A